A numerical study of aerosol effects on electrification of thunderstorms. (February 2017) - Tan, Y.B.; Shi, Z.; Chen, Z.L.; Peng, L.; Yang, Y.; Guo, X.F.; Chen, H.R.
Abstract: Numerical simulations are performed to investigate the effect of aerosol on microphysical and electrification in thunderstorm clouds. A two-dimensional (2-D) cumulus model with electrification scheme including non-inductive and inductive charge separation is used. The concentration of aerosol particles with distribution fitted by superimposing three log-normal distributions rises from 50 to 10, 000 cm −3 . The results show that the response of charge separation rate to the increase of aerosol concentration is nonmonotonic. When aerosol concentration is changed from 50 to 1000 cm −3, a stronger formation of cloud droplet, graupel and ice crystal results in increasing charge separation via non-inductive and inductive mechanism. However, in the range of 1000–3000 cm −3, vapor competition arises in the decrease of ice crystal mixing ratio and the reduction of ice crystals size leads to a slightly decrease in non-inductive charge rate, while inductive charging rate has no significant change in magnitude. Above aerosol concentration of 3000 cm −3, the magnitude of charging rate which keeps steady is insensitive to the increase in aerosol concentration. The results also suggest that non-inductive charge separation between ice crystal and graupel contributes to the main upper positive charge region and the middle negative charge region. Inductive graupel–cloud droplet charge separation, on the other hand, is found to play an important role in the development of lower charge region. Highlights: A cloud model with detailed activation and electrification process is used. We investigate the influence of aerosols on electrification in thunderclouds. The effect of aerosols concentration on charge separation is non-linear. The magnitude of charging rate keeps steady at very high aerosol concentration.